Kajian Kebutuhan Irigasi Sawah di Lapangan Daerah Irigasi Cihea Kabupaten Cianjur - Sutoyo, Sutoyo; Purwanto, M. Y. J.; Arif, Chusnul; Saptomo, S. K.; Heryansyah, Arien (Jurnal Komposit: Jurnal Ilmu-ilmu Teknik Sipil, 2025)
Indonesia is known as an agricultural country because most of its people cultivate rice in rice fields. BPS through the area survey framework (KSA) stated that the total harvest area in 2022 was 10.45 million hectares. This large area is very likely to cause inefficient water use in rice cultivation considering that most of the cultivation is carried out by inundation. Measurement of irrigation water needs in rice fields has been carried out mostly in the analysis stage, no detailed measurements have been found in evaluating irrigation water needs in rice fields. Evaluating the need for irrigation water in rice fields can easily be done with a water balance approach that considers all aspects of both incoming and outgoing water. This study aims to examine the components of irrigation water needs in the land preparation period. The study was conducted on rice plots equipped with several measuring instruments. Measuring water discharge in and out using CTF, weather data using AWS, and percolation measurements in the field. Measurement of water demand in rice fields on the plot resulted in a total inflow value of 195.38 mm and rainfall of 40.40mm. The total value of evapotranspiration occurred was 104.11 mm, the percolation value was 54.00 mm and the discharge out value was 29.59 mm, so the water loss was 48.08 mm (24.61%)